Revisiting the relationship between organizational commitment and professional commitment: a case study of academicians in a private educational institution - Abd Rahman, Nik Mutasim; Alias, Mohamad Adnan; Maulan, Suharni (Universiti Utara Malaysia, 2006)
Many studies have dwelled on various issues related to the concept of commitment. One particular issue concerns the relationship between organizational commitment and professional commitment. Between these foci of commitments, the issue has been whether both are compatible or in confliect with each other. The nature of the relationship between these variables is worth noting as it may have impact on the behaviour of individuals in organizations and hence, the formulation and practice of human resource policies in these organizations. This paper reports the findings of a study conducted to investigate this issue of compatibility or conflict between the variables. The unit of analysis were academicians employed in a private reserach institution in Malaysia. The result of the mail survey revealed the existence of a commitment dilemma within the sample. No significant correlations were recorded between professional commitment and the various dimensions of organizational commitment. Additionally, professional commitment and organizational commitment correlated significantly with intent to stay in the profession and intent tostay with the organization, respectively. Directions for future research were also discussed.